Implementasi Integrated Marketing Communcation dalam Meningkatkan Jumlah Penginap di Grand Wahid Hotel Salatiga - Laksana, Fiqih Uta; Kristiyani, Dian Novita (Jurnal Ilmu Komunikasi PROGRESSIO, 2024)
Salatiga is a city in Central Java that tourists often visit. It is located between Mount Merbabu and Mount Telomoyo, Salatiga, and has a cool climate suitable for tourism. The number of hotels is increasing yearly, and competition in the hotel industry is getting tighter. Integrated Marketing Communication is the key to increasing the number of hotel stays. This study aimed to evaluate the implementation of IMC at Grand Wahid Hotel Salatiga and its impact on the number of stays. This research method uses a qualitative method with a descriptive approach. Data collection uses interviews, observations, and techniques. The study results indicate that advertising and direct marketing components help increase the number of stays and the existence of Grand Wahid Hotel Salatiga.